An experimental investigation of liquid jets under low-speed crossflows - Mercan, Hatice; Nabati, Mehdi; Bedir, Hasan; Anlas, Gunay (YILDIZ TECHNICAL UNIV, 2024)
This study presents the breakup mechanisms and droplet features of a liquid jet introduced into a low-speed cross air flow. The main aim of this study is to investigate the spray behavior of water when exposed to a uniform crossflow of air at very low velocities. A shadow sizing system is employed to collect comprehensive data for analyzing the interactions between liquid jets and crossflowing air. Three different nozzles were used to examine the distribution, penetration, and breakup characteristics of water jets in an air crossflow. It is worth highlighting that the Weber number in this experiment was maintained at a very low level. Both the jet Weber number (1.3 < We(j) < 119) and the gas Weber number (0 < We(g) < 1), along with the momentum flux ratio (2 < q < 14400), are crucial dimensionless parameters significantly affecting various droplet properties such as size, velocity, shape, and breakup behavior. This study investigates the structural features, trajectory of the jet, and duration of breakup near the nozzle. Subsequently, the experimental results are tabulated for future numerical and analytical studies. As the air crossflow velocity increases, the liquid jet bends in the direction of the airflow. The breakup length decreases with increasing air velocity. The nozzle with medium diameter shows the maximum dimensionless breakup length. At a constant air velocity, the breakup length initially increases and then decreases with an increasing momentum flux ratio. Higher liquid flow rates result in a higher density of smaller droplets. The liquid jets shift upstream with increasing q values; however, due to the wide range of q values, existing empirical relations in the literature fail to accurately predict this behavior.
Keywords: Droplet Formation; Gaseous Crossflow; Liquid Jet; Momentum Flux Ratio; Shadow Graph; Spray Penetration; Weber Number; PRIMARY BREAKUP; ATOMIZATION; PENETRATION; SIMULATION; INJECTION; Thermodynamics